Cough-independent production of viable Mycobacterium tuberculosis in bioaerosol. (January 2021) - Patterson, Benjamin; Bryden, Wayne; Call, Charles; McKerry, Andrea; Leonard, Bryan; Seldon, Ronnett; Gqada, Melitta; Dinkele, Ryan; Gessner, Sophia; Warner, Digby F.; Wood, Robin
Abstract: Background: Symptoms of infectious respiratory illnesses are often assumed to drive transmission. However, production and release of Mycobacterium tuberculosis ( Mtb) bioaerosols is poorly understood. We report quantitation of Mtb exhaled during specific respiratory manoeuvres. Methods: Direct capture of nascent bioaerosol particles and indirect collection of aged particles was performed in 10 healthy subjects. Indirect and direct capture of exhaled viable Mtb bacilli was compared in 38 PTB patients and directly captured viable Mtb during cough and bronchiole-burst manoeuvres in 27 of the PTB patients. Results: Direct sampling of healthy subjects captured larger bioaerosol volumes with higher proportions of 2–5 μm particles than indirect sampling. Indirect sampling identified viable Mtb in 92.1% (35 of 38) of PTB patients during 60-min relaxed breathing, median bacillary count 7.5 (IQR: 3.25–19). Direct sampling for 10-min identified Mtb in 97.4% (37 of 38) of PTB patients with higher bacilli counts (p < 0.001), median 24.5 (IQR:11.25–37.5). A short 5-min sampling regimen of 10 coughs or 10 bronchiole-burst manoeuvres yielded a median of 11 (IQR: 4–17) and 11 (IQR: 7–17.5) Mtb bacilli, respectively (p = 0.53 ) . Conclusions: Peripheral lung bioaerosol released through deep exhalations alone contained viable Mtb suggesting non-cough transmission is possible in PTB.